Poverty In Nigeria and Government Efforts Towards Its Alleviation - Kura, Shuaibu Shehu; Viswanathan, K. Kuperan; Ishak, Suhaimi (UUM Press, 2019)
Nigeria, the most populous country not only in Sub-Saharan Africa but the continent as a whole, is highly endowed with natural resources, and being the 6th largest crude oil exporter in the world, its people are paradoxically wallowing in excruciating poverty. Historically, the trend of poverty in Nigeria is that of the upsurge. In 1980, for instance, the number of people living in poverty increased from 27% to 46% in 1985 and from 55% in 2004 to 61% in 2010 and 64% in 2013 (World Bank, 2013). Consequently, the need arises for concerted effort to be made to tackle the menace of poverty in the country. Thus, several poverty alleviation programmes were undertaken by the Federal Government of Nigeria (FGN) as an indication of its commitment to alleviate poverty in the country. Reviewing relevant literature, we evaluate poverty alleviation programmes in this paper. We conclude that despite enormous resources allocated to poverty elevation programmes, poverty levels did not decline but has increased over time. This failure is explained by corruption, overlapping functions and rivalry among executing agencies, as well as political interference. Recommendations for improving poverty alleviation programmes and making them more effective are provided in this paper.